2007
DOI: 10.1021/ed084p556
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Structures from 1H NMR Spectra: Education Aided by Internet Programs

Abstract: The article presents the way in which freeware Internet programs can be applied to teach 1H NMR spectroscopy. The computer programs described in this article are part of the educational curriculum that explores spectroscopy and spectra interpretation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…This was the students’ first exposure to the analysis of complex mixtures via GC–MS, and they were initially overwhelmed by the myriad peaks on the chromatograms. In future years, we recommend an in-class activity prior to the lab exercise that has students analyze such complex mixture data by comparing retention times and ionization spectra, similar to ways in which we teach NMR, or as Pacot et al recently suggested, through first analyzing a set of data from a standard mixture …”
Section: Assessment Implications and Limitationsmentioning
confidence: 99%
“…This was the students’ first exposure to the analysis of complex mixtures via GC–MS, and they were initially overwhelmed by the myriad peaks on the chromatograms. In future years, we recommend an in-class activity prior to the lab exercise that has students analyze such complex mixture data by comparing retention times and ionization spectra, similar to ways in which we teach NMR, or as Pacot et al recently suggested, through first analyzing a set of data from a standard mixture …”
Section: Assessment Implications and Limitationsmentioning
confidence: 99%
“…We are aware of no existing peer-reviewed literature that examines spectroscopic analysis through the lens of argumentation. Prior reports instead focus on strategies believed to foster “problem solving skills”, describing the differences between expert and novice analyses of spectroscopic data, or characterizing invalid chemical assumptions and heuristics that are believe to constrain student reasoning during IR and 1 H NMR spectroscopic interpretation . We can find no published strategies that contain strong evidence that a particular intervention improves student ability to argue from spectroscopic evidence; that is, extant literature does not compare the success of large student cohorts engaged in the described intervention with those not so engaged.…”
Section: Introductionmentioning
confidence: 98%
“…Although the concept of introducing computer-assisted analysis for the interpretation of NMR spectra is not new, [11] there have been many improvements in the resources made available to both students and instructors including computer modelling software for chemical shift calculations based on molecular electrostatic potential, [12] neural network and Hierarchical Organization of Spherical Environments (HOSE) code, [13] quantum mechanics, [14] as well as easy to use internet software and databases. [15,16] The purpose of Computer-Assisted Structure Elucidation (CASE) software is to use the expertise of the spectroscopist and known structural rules to determine and/or confirm molecular structures of unknown compounds in a timely manner. The software aims to eliminate potential chemist or analyst preconceived bias when analyzing NMR spectra and propose likely candidates based solely on the spectroscopic information available.…”
Section: Introductionmentioning
confidence: 99%
“…As the problems for modern day chemists/analysts become more challenging with respect to resources, time, and structure complexity, it is imperative that more chemists become trained with the latest tools available to them in order to work more efficiently. Although the concept of introducing computer‐assisted analysis for the interpretation of NMR spectra is not new, there have been many improvements in the resources made available to both students and instructors including computer modelling software for chemical shift calculations based on molecular electrostatic potential, neural network and Hierarchical Organization of Spherical Environments (HOSE) code, quantum mechanics, as well as easy to use internet software and databases …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation